Godly heathens : a novel - Edgmon, H. E. (New York : Wednesday Books, 2023)
Seventeen-year-old Gem Echols hides their mental health challenges and mysterious dreams in the small town of Gracie, Georgia, but when a newcomer reveals a shocking claim of being reincarnated gods together, Gem's life takes a perilous turn as they embark on a deadly adventure, where their past and present collide.
Series and volume numbering from Goodreads.com.
Ages 14-19.
Keywords: Magic -- Juvenile fiction; Gods -- Juvenile fiction; Seminole Indians -- Juvenile fiction; Indians of North America -- Juvenile fiction; Gender-nonconforming people -- Juvenile fiction; Reincarnation -- Juvenile fiction; Transgender people -- Juvenile fiction; Magic -- Fiction; Gods -- Fiction; Seminole Indians -- Fiction; Indians of North America -- Fiction; Gender identity -- Fiction; Magic -- Fiction; Gods -- Fiction; Seminole Indians -- Fiction; Indians of North American -- Fiction; LGBTQ+ people -- Fiction; Young adult fiction; Transgender fiction; Queer fiction; Fantasy fiction; Romance fiction; Novels